Risk factors and incidence of contrast induced nephropathy following coronary intervention (Medical Journal of Indonesia, 2008)
Contrast induced nephropathy (CIN) is one of important complication of contrast media administration. Its incidence and risk factors among Indonesian patients undergoing coronary intervention has not been reported yet. CIN was defined as increasing of serum creatinine by 0.5 mg/dl or more in the third day following contrast media exposure. Of 312 patients undergoing coronary intervention, 25% developed CIN. Patient-related risk factors comprised of hypertension, diabetes mellitus, NYHA class, proteinuria, serum creatinine > 1.5 mg/dl and ejection fraction ≤ 35%. Contrast-related risk factors comprised of contrast media volume > 300 ml, contrast media type. However, our final model demonstrated that only hypertension [Hazard ratio (HR) = 2.89, 95% confidence intrval (CI) = 1.78 to 4.71, P = 0.000], diabetes mellitus (HR = 3.09, 95% CI = 1.89 to 5.06, P = 0.000), ejection fraction (EF) ≤ 35% (HR = 2.92; 95% CI = 1.72 to 4.96; P = 0.000), total contrast volume > 300 ml (HR = 7.73; 95% CI = 3.09 to 19.37; P = 0.000) and proteinuria (HR = 14.96; 95% CI = 3.45 to 64.86; P = 0.000) were independent risk factors of CIN. In conclusion, CIN developed in 25% of patients undergoing coronary intervention. The independent risk factors of CIN included hypertension, diabetes mellitus, EF ≤ 35%, contrast volume > 300 ml and proteinuria. (Med J Indones 2008; 17: 131-7)